A comunicação dos valores da marca através de eventos: um estudo de caso da marca Oi - Magalhaes, Lorena Lourenço (2008)
The objective, in this study, was to verify if events, while communication tool, transmits brand value. The specific objectives had searched to still verify, if events generate intention of purchase in relation to the brand. The study if it characterized as exploratório, a time that the problematic one needed to get information you add and was carried through with the aid of techniques of qualitative and quantitative research. For the concretion of the objectives of the research revision of literature on the marketing concepts was carried through, communication, events, brand and brand value. To complement the theoretical revision a study of case of the mark of Oi telephony was lead, through research of field next to the participant public of an event promoted for the brand. The results of this study had shown that: the planning of the event in study, that had promocionais ends, occurred of satisfactory form and provided brand souvenir; the event positively marked the public who considered propensity to the purchase of products of the brand; the values of the brand, as well as its positioning, had been perceived by the public.